Analysis of Factors Influencing the Lack of Motivation of Stigmatized Students in Learning English with a Psychological Approach at MA Muhammadiyah Suprapto in Bengkulu City - Desva Andusti; Washlurachim Safitri; Dian Susyla (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Learning motivation is a critical internal drive determining academic success, yet it remains a significant challenge for stigmatized learners. This study aims to identify the psychological factors contributing to low learning motivation among stigmatized students and examine the effectiveness of a psychological-empathic approach in enhancing their motivation in English language learning. Conducted at MA Muhammadiyah Suprapto Bengkulu City, this descriptive qualitative research involved eight students as research subjects. Data were collected through classroom observations, semi-structured interviews, and documentation during the School Field Experience Program (PLP II). The findings reveal that low motivation is driven by internal factors such as emotional pressure from unstable family backgrounds and low self-esteem and external factors, specifically negative social labeling and a lack of emotional support. However, the implementation of a psychological approach, characterized by active listening, emotional validation, and empathetic interpersonal interactions, significantly reduced academic anxiety and fostered students' self-confidence. The results showed a notable shift in student behavior from passivity to active engagement and increased participation in communication-based tasks. This study concludes that a psychological-empathic approach is a central factor in restoring the learning enthusiasm of stigmatized students by creating a safe and inclusive emotional climate. These findings suggest that emotional recovery through humanistic teacher-student relationships is a fundamental prerequisite for academic engagement in foreign language learning.